Challenges in the Philippine Educational System and its Impact Towards Teachers' Instruction Strategies and Professional Growth - Frianeza, Ederliza D.; Maravilla, Haide D.; Relox, Realyn D.; Dagaraga, Sarah Jane Salvacion L.; Cruz, Cristel A. Dela; Solomon, Eleonor H.; Mohammad, Nhelbourne K. (Journal of Pedagogy and Education Science, 2024)
Challenges in the education system significantly impact the teachers' strategies and methods of instruction and their efforts for professional growth. The challenges bring difficulty in achieving the desired outcomes; however, these cases create an opportunity for the teachers to think of the best strategy to give quality education and a positive future for Filipino learners. The article revealed that various educational system problems affect the quality of instruction teachers provide for the learners, like low government budget for education and the effect of the recently implemented K-12 curriculum. On the other hand, the article reviews the importance of the government's support for continuous professional development (CPD) of teachers.